2021
DOI: 10.3390/polym13060922
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Argan Shell Wastes in Wood Plastic Composites with Biobased Polyethylene Matrix and Different Compatibilizers

Abstract: The present study reports on the development of wood plastic composites (WPC) based on micronized argan shell (MAS) as a filler and high-density polyethylene obtained from sugarcane (Bio-HDPE), following the principles proposed by the circular economy in which the aim is to achieve zero waste by the introduction of residues of argan as a filler. The blends were prepared by extrusion and injection molding processes. In order to improve compatibility between the argan particles and the green polyolefin, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 89 publications
(124 reference statements)
1
22
0
Order By: Relevance
“…Finally, the band at 1462 cm −1 is due to the C-H bending vibration, while the absorption peaks at 1862 and 1784 cm −1 are attributed to the anhydride groups. Similar results have been reported by Jorda-Reolid et al [84] for this type of natural compatibilizer.…”
Section: Chemical Structure and Infrared Spectroscopysupporting
confidence: 91%
“…Finally, the band at 1462 cm −1 is due to the C-H bending vibration, while the absorption peaks at 1862 and 1784 cm −1 are attributed to the anhydride groups. Similar results have been reported by Jorda-Reolid et al [84] for this type of natural compatibilizer.…”
Section: Chemical Structure and Infrared Spectroscopysupporting
confidence: 91%
“…On the contrary, the rest of samples had positive values due to the characteristic brown colour of chia seed flour [ 99 ]. Higher values of a* coordinate have been reported by Jorda-Reolid et al [ 100 ] who employed Bio-HDPE with argan shell wastes. In this study a higher a* value above 5 was reported, thus a reddish brown colour was obtained [ 100 ].…”
Section: Resultsmentioning
confidence: 71%
“…Higher values of a* coordinate have been reported by Jorda-Reolid et al [ 100 ] who employed Bio-HDPE with argan shell wastes. In this study a higher a* value above 5 was reported, thus a reddish brown colour was obtained [ 100 ]. Referring to colour coordinate b*, it is an indicative of blue to yellow colours.…”
Section: Resultsmentioning
confidence: 71%
“…[ 47,63 ] It can be observed that Bio‐HDPE presents a glass transition temperature (identified by the peak of the γ‐transition) with a value of ‐115 °C and the α‐transition at a temperature of ≈50 °C, which are consistent with the results reported by Jorda‐Reolid, Gomez‐Caturla. [ 64 ] The addition of PPF leads to a small decrease in the glass transition temperature by about 3 °C, due to the increased interaction between the PPF particles and the matrix, as above‐mentioned. A decrease in the intensity of the γ‐relaxation peak can be observed due to the increased internal friction caused by the PPF, which restricts the movement of the polyethylene chains.…”
Section: Resultsmentioning
confidence: 92%